Influencing factors of early childhood teachers’ disaster preparedness - Lee, Young-Ran; Park, Sun-Nam; Lee, Mi-Ran; Nam, Eunjeong (Frontiers in Public Health, 2023)
The risk of disasters and infectious diseases continues to persist in modern times. Children are a vulnerable group in disaster prevention and management due to their limited ability to cope on their own. Hence, the role and disaster preparedness capacity of early childhood teachers (ECTs) is vital for children's protection.Objectives: This study aims to explore how ECTs can improve their personal resilience to adapt to and overcome disasters as part of early childhood education and care (ECEC). To this end, this study examined the effects of ECTs' self-efficacy, resilience, disaster awareness, COVID-19 stress, and work-related stress on their disaster preparedness.Results: According to the outcomes of disaster preparedness of ECTs based on their general and job characteristics, full-time employees and principals scored significantly higher in work-related disaster preparedness (WrDP) compared to part-time workers and general and assistant teachers, respectively. Resilience and WrDP were identified as influencing factors of general disaster preparedness (GdP), with an explanatory power of 26.4%. GdP and self-efficacy were identified as influencing factors of WrDP, with an explanatory power of 25.7%.Discussion: According to the findings, ECTs' self-efficacy and GdP must be improved, followed by developing strategies to strengthen their resilience and WrDP. Doing so would ensure the safety and disaster preparedness of ECTs and infants who have low self-care capacity.